Removal of metal cations from wastewater using recycled wool-based non-woven material - MAJA RADETIC; DARINKA RADOJEVIC; VESNA ILIC; DRAGAN JOCIC; DRAGAN POVRENOVIC; BRANISLAV POTKONJAK; NEVENA PUAC; PETAR JOVANCIC (Journal of the Serbian Chemical Society, 2007)
In this study, the effect of low-temperature air plasma, biopolymer chitosan and hydrogen peroxide treatment of recycled wool-based non-woven material on metal cation uptake was investigated. Recycled wool-based material either as an untreated or modified material showed ability to bind all investigated metal cations in the following order: Pb2+>Cu2+>Zn2+>Co2+. Material performed good selectivity due to distinct sorption rates of studied metal cations.